Effectiveness of Heat Therapy on Musculoskeletal Pain Before and After Exercise Therapy in Females - Qadeer, Ummara; Aftab, Anan; Zahra, Iman (UNUSA Press, 2020)
Objective: To compare whether heat therapy (moist heat pack) is more effective before exercise therapy or after exercise therapy in chronic MSK pain in females. Design Randomized clinical trial study. Methodology: This study is conducted in Abbas institute of medical sciences Muzaffarabad and Muzaffarabad physiotherapy clinic Muzaffarabad.40 female patients with chronic MSK pain are recruited in the study and a questionnaire-based survey was carried out. A self-structured questionnaire is used for demographic details. For screening of chronic MSK pain short form of Orebro pain questionnaire is used. A numeric rating scale in both groups is used to check the intensity of pain. Result: The results showed that between group A and B there was no significant difference. But clinically group B showed more improvement than group A.Both groups showed improvement after treatment. Conclusion: The application of heat therapy (moist hot pack) was found to be more effective after exercises than its use before exercises to improve pain in females with chronic musculoskeletal pain.